Constructing Carbon Fiber Motion-Detection Loops for Simultaneous EEG–fMRI - Abbott, David F.; Masterton, Richard A. J.; Archer, John S.; Fleming, Steven W.; Warren, Aaron E. L.; Jackson, Graeme D. (Frontiers in Neurology, 2015)
One of the most significant impediments to high-quality EEG recorded in an MRI scanner is subject motion. Availability of motion artefact sensors can substantially improve the quality of the recorded EEG. In the study of epilepsy, it can also dramatically increase the confidence one has in discriminating true epileptiform activity from artefact. This is due both to the reduction in artefact and the ability to visually inspect the motion sensor signals when reading the EEG, revealing whether or not head motion is present. We have previously described the use of carbon-fibre loops for detecting and correcting artefact in EEG acquired simultaneously with MRI. The loops, attached to the subject’s head, are electrically insulated from the scalp. They provide a simple and direct measure of specific artefact that is contaminating the EEG, including both subject motion and residual artefact arising from magnetic field gradients applied during MRI. Our previous implementation was used together with a custom-built EEG-fMRI system that differs substantially from current commercially available EEG-fMRI systems. The present technical note extends this work, describing in more detail how to construct the carbon-fibre motion detection loops, and how to interface them with a commercially available simultaneous EEG-fMRI system. We hope that the information provided may help those wishing to utilise a motion-detection / correction solution to improve the quality of EEG recorded within an MRI scanner.